High occurrence of β-lactamase-producing Salmonella Heidelberg from poultry origin - Souza, Andrei I.S. [UNESP]; Saraiva, Mauro M.S. [UNESP]; Casas, Monique R.T.; Oliveira, Gustavo M. [UNESP]; Cardozo, Marita V. [UNESP]; Benevides, Valdinete P. [UNESP]; Barbosa, Fernanda O. [UNESP]; Freitas Neto, Oliveiro C.; Almeida, Adriana M. [UNESP]; Junior, Angelo Berchieri [UNESP] (Public Library of Science (PLoS), 2020)
Salmonella Heidelberg is commonly reported in foodborne outbreaks around the world, and chickens and poultry products are known as important source of these pathogen. Multidrugresistant S. Heidelberg strains are disseminated into poultry production chair, which can lead to severe clinical infections in humans and of difficult to treat. This study aimed at evaluating the β-lactam susceptibility and genotypic relatedness of Salmonella Heidelberg at Brazilian poultry production chain. Sixty-two S. Heidelberg strains from poultry production chain (poultry, poultry meat and poultry farm) were used. All strains were evaluated to antimicrobial susceptibility by diffusion disk test, as well as β-lactam resistance genes. Genotypic relatedness was assessed by Pulsed-Field Gel Eletrophoresis, using Xba1 restriction enzyme. Forty-one strains were characterized as multidrug-resistant according to phenotype characterization. The resistance susceptibility revealed 31 distinct profiles, with higher prevalence of streptomycin (61/62), nalidixic acid (50/62), tetracycline (43/62) and β-lactam drugs (37/62). blaCMY-2 was the more frequent β-lactamase gene found (38/62); other resistance genes found were blaCTX-M (2/62), blaSHV (3/62) and blaTEM-1 (38/62). No carbapenemase genes was found. The Pulsed-Field Gel Electrophoresis showed 58 different profiles. Strains with a larger number of antimicrobial resistance were grouped into ten major clusters apart from others. The spread of resistance by ampC continues to rise, thereby turning concern to public health, since the β-lactam antimicrobials are used as a therapeutic treatment in humans.